The role of serum IL-6 in colorectal cancer patients and it’s relationship with serum CEA level - Al-Ghurabi, Batool H.; Al-Saady, Luma G.; Al-Hassan, Ahmed A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The role of cytokines in cancer immunity and carcinogenesis in general has been well established, which play an important role in pathogenesis of many solid cancer. This study aimed to shed light on the possible role of IL-6 in pathogenesis of CRC and its relationship with serum CEA level. Patients and methods: This study covered 50subjects. It comprised of 30 patients with CRC, compared with 20 healthy normal controls. Serum IL-6 and CEA analysis were performed by ELISA. Results: This study revealed a significant elevation in serum IL-6 level among CRC patients (16.2 pg/ml) in comparison to that of healthy control (4.8 pg/ml) (p<0.001). As well as an interesting significant increase of mean serum CEA level in CRC patients (7.5± 6.62 ng/ml) as compared to healthy control (2.4±0.90 ng/ml). On the other hand there was strong linear correlation between serum CEA level and serum IL-6 level p<0.001. Conclusion: There are a significant correlation between the elevation of the serum IL-6 and CEA levels and the progression of this cancer. Moreover, positive association was found between IL-6 and CEA and this may help us to understanding the pathogenesis of this disease and ultimately may be use in the development of a new therapeutic technique.